Risk shifting in the US banking system: An empirical analysis - Duran, Miguel A.; Lozano-Vivas, Ana (Journal of Financial Stability, 2014)
This paper contributes to the empirical literature on risk shifting. It proposes a method to find out whether risk shifting is present in the banking industry and, if so, what type. The type of risk shifting depends on the group of debt holders to whom risk is shifted. We apply this method to the US banking sector in 1998–2011. To study the relationship between risk shifting and the 2008 crisis, the sample is also split into pre-crisis, crisis, and post-crisis periods. Our results suggest that the same type of risk shifting is present in the entire sample and in the pre-crisis and crisis subsamples. We find no evidence of risk shifting after the crisis. Furthermore, holding capital buffers seems to disincentivize risk shifting. This finding appears to provide support for the conservative buffer included in Basel III.